Characterization of the reactive oxygen species and reactive nitrogen species defense system in berangan banana / Fung Shi Ming - Fung , Shi Ming (2022)
Musa spp. cv. Berangan banana (AAA) is one of the most susceptible cultivars to Panama disease which is caused by the hemibiotrophic soil-borne pathogen Fusarium oxysporum f. sp. cubense (FOC). Panama disease, also known as Fusarium wilt causes great losses to global banana production. It is crucial to study the defense mechanism of banana plants against this disease in order to facilitate future solutions for this devastating disease. In this study, two-month-old Berangan banana plants were infected by soaking the roots in Fusarium oxysporum f. sp. cubense (FOC) culture. The plants were harvested at intervals of 1, 2, 4, 6, 8 and 10 days following infection. The fungus infects the plants from the zone of differentiation in the roots or any existing wounds. Penetration of FOC into the root causes cell disintegration leading to ions reflux in plant cells and resulting higher lipid peroxidation. In this study, cellular damage was observed in infected roots, rhizomes and pseudostems through Field Emission Scanning Electron Microscope (FESEM). Hyphae and conidia of FOC as well as tylose formation in the vascular bundle were visible. Increased levels of reactive oxygen species (ROS) such as superoxide anions (O2˙ˉ), hydrogen peroxide (H2O2), hydroxyl radicals (•OH) was one of the earliest responses observed in infected samples. Enzymes responsible for ROS synthesis, NADPH oxidase, were also up-regulated, which explains the oxidative burst at the pathogen attacking site, roots, and other parts of the plants, pseudostems and leaves at later stages of infection. ROS scavenging enzymes, superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), peroxidase (POD), ascorbate peroxidase (APX), and glutathione reductase (GR) play an essential role in monitoring the ROS level. A sharp increase in the ROS level and enzymatic activities were observed in the infected plants. The increment of ROS was biphasic whereas the ROS scavenging enzyme activities increased initially and decreased at later stages. Secondary metabolites such as phenolic compounds were also reported to be able to scavenge the harmful radicals in order to protect the host plants from fungal invasion. Methanol extract of the FOC infected Berangan banana plant roots, pseudostems and leaves were assessed for DPPH radicals scavenging activity, reducing power assay, total antioxidant activities, total flavonoid content and total polyphenol content. Results indicated that the amount of total phenolic and flavonoid compounds as well as antioxidant activity were higher in infected plants compared to healthy plants. However, the phenolic compound decreased at the later stage of infection. Subsequently, the phenolic and flavonoid profiles were analysed using liquid chromatography – mass spectroscopy (LCMS). Metabolites such as quinic acid, ferulic acid, caffeoyl glucose, p-coumaric acid, caffeic acid, p-hydroxybenzoic, kaempferol-rhamnose-hexose, quercetin, catechin, and rutin were identified with different concentration in different parts of the plants at different intervals.